1997
DOI: 10.1097/00005131-199704000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Plaster Cast Versus Percutaneous Pin Fixation for Comminuted Fractures of the Distal Radius in Patients Between 46 and 65 Years of Age

Abstract: The best anatomic and functional results were obtained by percutaneous pinning. Although the cost of pins and plaster treatment is significantly greater than plaster treatment, the author believes that the positive end result justifies the cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 0 publications
1
24
0
2
Order By: Relevance
“…These results conform with those in the literature where the reduction loss in volar tilt is one of the most important factors of worse functional outcomes. [21,22,25,26,27] The possibility of early functional treatment depends on the intraoperative influence of stability, complexity of the fracture pattern, quality of the bone, and age of the patient. [1] However, since K-wire fixation is not rigid, the patients often have to be immobilized in a plaster cast, generally for at least 4 to 6 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…These results conform with those in the literature where the reduction loss in volar tilt is one of the most important factors of worse functional outcomes. [21,22,25,26,27] The possibility of early functional treatment depends on the intraoperative influence of stability, complexity of the fracture pattern, quality of the bone, and age of the patient. [1] However, since K-wire fixation is not rigid, the patients often have to be immobilized in a plaster cast, generally for at least 4 to 6 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…These studies collectively included 653 patients (340 of whom received conservative treatment, and 313 of whom received internal fixation). In the present meta-analysis, 7 studies were reported in English and 3 were reported in Chinese, [11][12][13][14][15][16][17][18][19][20] and 9 studies included only adult patients (Fig. 1).…”
Section: Studies Included In Meta-analysismentioning
confidence: 99%
“…Reduction and plaster cast fixation [3,5,10,14,16,17,27], pins and plaster casts [11,14,19,25], open reduction and fixation with or without bone grafting [4,6,12,14], Rush pins [9,18], dynamic external fixation [2,15,24], bridging external fixation [1,6,11,20,23] and nonbridging external fixation [7,8,13]. In most studies, the external fixator has been found to be superior to plaster cast fixation in achieving a good end-anatomic result [1,6,7,8,23].…”
Section: Introductionmentioning
confidence: 99%